Penerapan Analisis Kemampuan Berbahasa Ilmiah Mahasiswa dalam Mengkomunikasikan Isu Keberlanjutan pada Mata KuliahBahasa Indonesia - Desvi Emti (Al-Manar Journal of Public Administration and Management, 2026)
Scientific language skills are an important competency for students to convey academic ideas, including communicating sustainability issues. This study aims to analyze students' scientific language skills in communicating sustainability issues in Indonesian language courses. This study uses a qualitative descriptive approach with data sources in the form of scientific writing and students' academic communication activities. Data were collected through documentation, observation, and analysis of language use, argumentation, and the delivery of ideas based on sustainability issues. The results show that students have been able to use scientific language structures and academic terms related to sustainability, but there are still limitations in strengthening arguments with scientific data and references. Integrating sustainability issues into Indonesian language learning can improve academic communication skills while building students' awareness of the importance of sustainable development.